العوامل الإجتماعية المساهمة في بناء الشخصية الروائية عند جبرا إبراهيم جبرا: Contribution of Social Factors in building Jabra Ibrahim Jabra’s Novels’ characters - د. رابعة عمر حيات (Al Manhal Research Journal, 2024)
A novel cannot be remembered without remembering its characters, actually no novel can secure any place in reader’s memory if its characters are not strong and impressive. So the characters are the base and central point in any work of fiction from where you can move around and explore different factors which may affect the reality around us, as well as the streamy nature of life which keeps reacting to these factors. Among these factors are the social factors which play important role in building and developing the characters by the novelist. They are can be easily traced through characters way of thinking and behaving in different situations. Jabra Ibrahim Jabra also used those factors to build the characters in his novels. He dedicated major space to village and family as the most influential in developing his characters. This paper will aim at studying these factors and how far their contribution helped Jabra Ibrahim Jabra make his characters unique.